Characterization of Wp-type of spaces involving fractional Fourier transform - Upadhyay, Santosh Kumar; Kumar, Anuj (Springer International Publishing, 2015)
The characterizations of Wp-type of spaces and mapping relations between W- and Wp-type of spaces are discussed by using the fractional Fourier transform. The uniqueness of the Cauchy problems is also investigated by using the same transform.
Keywords: convex functions; fractional Fourier transform; Gel’fand and Shilov spaces of type W; Lp-space